Nitrogen and sulfur effects on hard winter wheat quality and asparagine concentration and survey of Kansas soil sulfur conditions - Wilson, Tara Leanne (Kansas State University, 2020)
Soil sulfur (S) deficiency is becoming increasingly common throughout the U.S. due to The Clean Air Act of 1990; S deficiency is typically found in high sand and low organic matter soils and looks very similar to nitrogen deficiency with stunted growth and chlorosis. Over application of N when there is a S deficiency has shown to be detrimental to wheat quality. Sulfur deficiency is detrimental to baking quality due to its effects on formation of disulfide bonds. These bonds are formed from the sulfhydryl groups of cysteine, which influence viscoelasticity of dough. Soil S deficiency can also lead to an increase of free asparagine concentration which indicates acrylamide forming potential of baked products. Acrylamide is a potential carcinogen; S fertilization has been shown to decrease acrylamide forming potential in wheat flour. Therefore, the objectives of this study were to: i) determine the effect of genotype, N, and S fertility on overall wheat quality and rheological characteristics; ii) determine the typical range of asparagine in wheat grain in Kansas: and iii) determine the influence of S availability in soils on asparagine in wheat grain. In the first study we found that in a soil with low S availability, S fertility significantly increased overall grain quality and rheological characteristics as well as increasing yield. Protein composition was evaluated by the ratio of total polymeric/ total monomeric protein using high performance liquid chromatography. In both years, the ratio of polymeric to monomeric protein was increased by sulfur fertilization. Solvent retention capacity (SRC) was evaluated using the whole grain lactic acid-sodium dodecyl sulfate solvent retention test (lactic acid- SDS SRC). In 2018, S application increased the SRC from 217% to 308%. Sulfur application increased average farinograph stability from 9.2 min to 14.6 min. Farinograph stability was effectively predicted by the SRC test (R²=0.78). Free asparagine concentration decreased significantly in both years across all genotypes when S was applied. Although, in Chapter 2 we found that poor wheat quality in a S deficient soil was increased with S fertilizer application, we did not find a strong correlation between available S in the soil and wheat quality or free asparagine concentration in Chapter 3. In 2018 a S sufficient location, Ashland had the highest free asparagine concentration (37 μmol/g) which was likely due to hot dry weather during grain fill. Thus, further investigation of factors influencing free asparagine in winter wheat is necessary for us to have a better understanding of how to decrease the risk of elevated levels. Information from this study will help winter wheat producers in the Great Plains diagnose sulfur deficiency and determine best practices for increasing grain quality and decreasing free asparagine concentration.
Keywords: Asparagine; wheat quality; sulfur fertility